(untitled) (Pragyaratna प्रज्ञारत्न, 2025)
It brings us great joy to share the current edition (Vol. 7, No.1) of Pragyaratna, an academic publication of TUTA, Mahendra Ratna Campus, Tahachal Unit. This is the foruth online issue since its first publication in 2019. To keep ourselves abreast of the technological advancements in academic publishing, we have started online submissions through the Journal Publishing Practices and Standards (JPPS) process with this issue. A disciplinary academic publication forum, this issue of Pragyaratna features 16 articles from across diverse streams, principally within education. The articles in the current issue exhibit diversity in subject areas, themes and languages. The collection of articles spans diverse subject areas, including Mathematics Education, Health and Population Education, Nepali Language Education, Economics Education, Core Education, and Nepali Education. Thematically, the article covers a wide range of foundational and emerging issues such as environmental sustainability, educational financing, learning motivations, formation of teacher identity, integration of ethnoknowledge into pedagogy, youth migration, and second language teaching. We expect that this thematic diversity will enrich our perspectives on macro- and micro-level issues pertinent to the widening landscape of teacher education. In terms of language, this issue contains articles in both English and Nepali, which ensures the equal participation of the faculty members who write in Nepali in knowledge construction and sharing. All the articles published in this volume underwent a rigorous review and editing process. The articles were first desk-reviewed by the editorial team in close alignment with the journal guidelines. Only the articles that passed the first phase of review were forwarded to the blind peer review process. The rest of the articles were either returned to authors for correction and resubmission or rejected. The articles that passed the peer review process qualified for further processing. Each article was subject to multiple rounds of review between authors and editors to ensure academic integrity. We hope that the articles in this issue will contribute to the ongoing scholarly dialogue, particularly within the faculty of education, and offer valuable insights for teaching, training and research. We are thankful to the authors who trusted Pragyaratna and submitted their valuable work for publication. We are thankful to them for their patience and cooperation during the entire publication process. Our deep gratitude to all reviewers for their scholarly contributions to enhancing the quality of the articles. Finally, we cannot end this editorial without acknowledging the relentless technical and academic support from Assistant Professor Parshu Pam Upadhayaya Department of Information Communication Technology, Mahendra Ratna Campus, Tahachal. Editorial Board Pragyaratna